GENERATIONAL GUIDANCE: THE INTERPLAY OF PEER AND PARENTAL INFLUENCE IN SAUDI YOUNG FEMALE CONSUMERISM - Al-Farsi, Ahmad Khalid; Al-Mohammed, Sara Noura (Research Journal of Economics and Sustainable Development, 2024)
Consumer behavior is a critical concern for producers and marketers to understand as it has a significant impact on the success or failure of a product or service. This study examines the influence of parental and peer power on the purchase decisions of young female consumers in Saudi Arabia. The study utilized social power theory, and data was collected using a self-administered survey distributed to 285 young female Saudi consumers. The findings revealed high influence levels of parents' legitimate, referent, and reward power, while peer power was highest in areas of expertise, reward, and legitimate power. The results offer critical insights to producers and marketers on the importance of considering family and peer power in consumers' decision-making processes. The study highlights the overall importance of parental and peer power in consumer decision-making. The findings suggest that designing optimal marketing strategies for young female consumers requires considering the role of parents and peers in their purchasing decisions. Marketers targeting young female consumers in Saudi Arabia need to focus not only on consumers but also on the factors influencing their purchasing decisions. Overall, the study highlights that peer and parental power plays a significant role in consumer decision-making, which marketers need to consider when targeting young female consumers in Saudi Arabia.